A novel mutation in PRPF31, causative of autosomal dominant retinitis pigmentosa, using the BGISEQ-500 sequencer - Zheng, Yu (Int J Ophthalmol, 2018)
AIM: To study the genes responsible for retinitis pigmentosa. METHODS: A total of 15 Chinese families with retinitis pigmentosa, containing 94 sporadically afflicted cases, were recruited. The targeted sequences were captured using the Target_Eye_365_V3 chip and sequenced using the BGISEQ-500 sequencer, according to the manufacturer's instructions. Data were aligned to UCSC Genome Browser build hg19, using the Burroughs Wheeler Aligner MEM algorithm. Local realignment was performed with the Genome Analysis Toolkit (GATK v.3.3.0) IndelRealigner, and variants were called with the Genome Analysis Toolkit Haplotypecaller, without any use of imputation. Variants were filtered against a panel derived from 1000 Genomes Project, 1000G_ASN, ESP6500, ExAC and dbSNP138. In all members of Family ONE and Family TWO with available DNA samples, the genetic variant was validated using Sanger sequencing. RESULTS: A novel, pathogenic variant of retinitis pigmentosa, c.357_358delAA (p.Ser119SerfsX5) was identified in PRPF31 in 2 of 15 autosomal-dominant retinitis pigmentosa (ADRP) families, as well as in one, sporadic case. Sanger sequencing was performed upon probands, as well as upon other family members. This novel, pathogenic genotype co-segregated with retinitis pigmentosa phenotype in these two families. CONCLUSION: ADRP is a subtype of retinitis pigmentosa, defined by its genotype, which accounts for 20%-40% of the retinitis pigmentosa patients. Our study thus expands the spectrum of PRPF31 mutations known to occur in ADRP, and provides further demonstration of the applicability of the BGISEQ500 sequencer for genomics research.